15‐1: High Resolution Display Data Transmission using Weak Sub‐color DWT. Issue 1 (28th June 2021) - Lee, Joonhee; Park, Dongwon; Ko, Namkon; Kim, Changgone; Yoon, Sooyoung
Abstract : As a resolution of display increases, it is necessary to process video data more efficiently and economically. In this paper, an advanced technique is proposed to reduce its data bandwidth in real time without any noticeable degradation in its image quality. By analyzing the frequency characteristics of an input image data with respect to its sub‐colors, a sub‐color data having relatively smaller proportion in high frequency which can be regarded as a 'Weak Sub‐color data' can be converted and reduced using the Discrete Wavelet Transformation (DWT). Some of the DWT‐transformed data is transmitted with the other non‐processed original sub‐color data to reduce its data size. This technique can provide a robust video system interface that reduces its transmission bandwidth up to 25% or more with improved image quality.